Pengenalan Bekam Sebagai Terapi Komplementer (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2025)
Complementary therapy is increasingly receiving attention as an alternative approach in supporting the healing process and improving the quality of life of the community. One of the therapies that is popular among the people is cupping, which is known as a traditional method with a spiritual basis and extensive health benefits. This community service activity aims to introduce cupping therapy and increase public understanding of the basic principles, benefits, and safety aspects in practice. The activity will be carried out in August 2025 by directly involving the community through the method of health education lectures and case discussions in the field. The counseling material includes the history of cupping, medical indications, implementation procedures, and the importance of maintaining the cleanliness of the device and the therapeutic environment. People's motivations in choosing complementary therapy, especially cupping include affordable cost factors, therapist friendliness, family support, religious beliefs, and belief in the effectiveness of natural remedies. The results showed a significant increase in the knowledge and awareness of the community, especially students, regarding cupping therapy as part of a safe and beneficial complementary approach. The conclusion of this activity emphasizes that education about complementary therapies, especially cupping, can be an effective strategy in expanding public health insights and encouraging the wise and responsible use of traditional therapies.